The importance to have building inspector for new house buyers / N.A M. Radzuan, W.S.Z W Hamdan, M.Y Hamid, M.A.Z. Arifin - Mohd Radzuan, Nor Amin; Wan Hamdan, Wan Samsul Zamani; Hamid, Md Yusof (2012)
Purpose: This paper is to identify the problems related to new house buyers. Issues related to low quality houses, defect liability period and purchasers’ right to be discussed in this research. In Malaysia the private sector and government agencies are responsible to develop new residential area. In general the government agencies to provide affordable homes for lower income group in considering that every people need a proper shelter for living. While private sector to meet the property market demand. The research adopts comprehensive literature reviews from numerous published sources such as journals, magazines, government reports, unpublished thesis and website document focusing on issues related to new house buyers. Methodology: This paper attempts to establish understanding the importance of right of new house buyers and to engage Building Inspector as third party to advice on building defects and specification. The paper expects that, Building Inspector will be recognised as a competent person to conform on workmanship, materials and building’s specification. In addition the paper intends to generate awareness among new house buyers on their rights to receive newly completed houses in acceptable standard, while its a duty of property developer to deliver the best for the purchaser.